Basics and security system in the national security strategy - Đukić Stanimir (Војно дело, 2017)
The term 'security' has changed its meaning throughout history. Nowadays there are many definitions of this term, which depend on the context in which it is used. In political sciences, particularly a science of international relations, security is one of the key concepts. This paper defines the concept of security, that is its different understanding (problem approach), as well as modern comprehension. Moreover, the protective function of the state and security are considered as an attribute and function of the state. The classification of security, as well as the theory of the security system, have also been considered by analyzing the theory of security and the concept and elements of the security system. Each system, including the security system, is characterized by its efficiency. Each country forms several large systems, subsystems and microsystems. There are vertical and horizontal links between them, through which they function as a global state and social system. In addition, the security system in the National Security Strategy of the Republic of Serbia has been analyzed, that is, the National Security Strategy has been defined as the main political and security document that reflects foreign and internal security policy, its determination to achieve and maintain national security of the state in the broadest sense of the term by its own security system built on the national potential and in cooperation with other systems and international security organizations.